Fuzzy Shortest Path Problem Based on Level 𝜆-Triangular LR Fuzzy Numbers - S. Elizabeth; L. Sujatha (Advances in Fuzzy Systems)
In problems of graphs involving uncertainties, the fuzzy shortest path problem is one of the most studied topics, since it has a wide range of applications in different areas and therefore deserves special attention. In this paper, algorithms are proposed for the fuzzy shortest path problem, where the arc length of the network takes imprecise numbers, instead of real numbers, namely, level 𝜆-triangular LR fuzzy numbers. Few indices defined in this paper help to identify the shortest path in fuzzy environment.